Perennial-GHG: A new generic allometric model to estimate biomass accumulation and greenhouse gas emissions in perennial food and bioenergy crops. (April 2018) - Ledo, A.; Heathcote, R.; Hastings, A.; Smith, P.; Hillier, J.
Abstract: Agriculture, and its impact on land, contributes almost a third of total human emissions of greenhouse gases (GHG). At the same time, it is the only sector which has significant potential for negative emissions through offsetting via the supply of feedstock for energy and sequestration in biomass and soils. Perennial crops represent 30% of the global cropland area. However, the positive effect of biomass storage on net GHG emissions has largely been ignored. Reasons for this include the inconsistency in methods of accounting for biomass in perennials. In this study, we present a generic model to calculate the carbon balance and GHG emissions from perennial crops, covering both bioenergy and food crops. The model can be parametrized for any given crop if the necessary empirical data exists. We illustrate the model for four perennial crops – apple, coffee, sugarcane, and Miscanthus – to demonstrate the importance of biomass in overall farm GHG emissions. Graphical abstract: Image 1 Highlights: Inconsistency in methods impedes quantification on net greenhouse gas emissions (GHG) of perennial crops. We present a generic model to calculate the carbon balance and GHG emissions from perennial crops, including examples. Different crops and management practices lead to very different emissions of GHGs, which can be either positive or negative. Under judicious management, perennials have potential for climate change mitigation.